INSTITUTIONAL TRAPS OF DOMESTIC HIGHER EDUCATION - Evgeniya L. Moreva (Статистика и экономика)
Development of domestic higher education system depends on the actual social and economic institutions as well as the effects of the previous ones. To overcome them the complex approach is required with the organizations mobilizing their own intellectual activity.